3a+6b are two terms of an expression
Oh, dude, it's like asking me for the cool, alternative name for your boring math problem. So, 3a plus 5 is basically the same as saying "three times a, plus five." It's just a fancier way of dressing up your numbers, you know?
It is an expression that can be simplified to: 3a-2b+c
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)
a + 7b + 2c
It is:12a
3a+6b are two terms of an expression
-2
Oh, dude, it's like asking me for the cool, alternative name for your boring math problem. So, 3a plus 5 is basically the same as saying "three times a, plus five." It's just a fancier way of dressing up your numbers, you know?
(5a+8) - (2a+4) =3a +4 To do this, simply subtract like terms. 5a-2a=3a and 8-4=4
It is an expression that can be simplified to: 3a-2b+c
The given expression can be simplified to: 3b-a
12a
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)
6a²b - 12ab²
7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a
a + 7b + 2c